Monitoring lightdriven oxygen insertion reactions into metal carbon bonds by LEDNMR spectroscopy - Ho,SKY; Ezeorah,C; Chari,S; SalehiReyhani,A; Britovsek,GJP (ChemPhotoChem, 2023)
The facile light-driven insertion reaction of oxygen into metal carbon bonds of the BPI (1,3-bis(2-pyridylimino)isoindole) complexes [Pt(BPI)Me] and [Pd(BPI)Me] has been investigated by LED-NMR in CDCl3. The initial insertion reaction leads to peroxo complexes [Pt(BPI)OOMe] and [Pd(BPI)OOMe], which undergo further reactions over time. Spectra were recorded at 1 minute time intervals, which enabled the tracking of the methyl substituent, which eventually generates formaldehyde (and methanediol) and methanol in almost equal proportions. Degradation of the solvent CDCl3 to phosgene and DCl in the presence of oxygen and light leads to several side reactions. DCl reacts with [M(BPI)Me] and [M(BPI)OOMe] to form [M(BPI)Cl], whereas phosgene reacts with insitu generated methanol to chloro methylformate and dimethyl carbonate.